고도비만이 동반된 폐쇄성수면무호흡증 환자에서 시행된 비만대사수술 1례 - 이상국(Sang Kuk Lee), 홍승노(Seung-No Hong), 정재현(Jae Hyun Jung), 최지호(Ji Ho Choi) (Sumyŏn--chŏngsin saengni, 2016)
Obstructive sleep apnea syndrome (OSAS) has negative effects on health, including increased mortality, risk of cardiovascular disease, and neurocognitive difficulties. OSAS is common in obese patients and obesity is an important risk factor of OSAS. A 41-year-old female OSAS patient with severe obesity (body mass index [BMI] ${≥}35$) who failed dietary weight loss underwent bariatric surgery. After surgery, there were improvements in BMI (from 36.9 to $31.7kg/m^2$) and polysomnographic data, including the apnea-hypopnea index (from 25.1 to 11.2 events/hr) and minimum SaO2 (from 69 to 82%). This case demonstrates that bariatric surgery may be an effective therapeutic option to reduce sleep-disordered breathing in severely obese patients with moderate OSAS. Bariatric surgery as a treatment option for OSAS should be considered in OSAS patients with severe obesity who failed dietary weight loss.